Of Philosophers and Kings : Political Philosophy in Shakespeare's Macbeth and King Lear - Craig, Leon Harold (Book collections on Project MUSE., 2001)
"This work argues that Shakespeare was as great a philosopher as he was a poet, and that his greatness as a poet derived even more from his power as a thinker than from his genius for linguistic expression. Accordingly, Leon Craig's interpretation of the plays - focusing primarily on Macbeth and King Lear, but including extensive comments on Othello, The Winter's Tale, and Measure for Measure - are intended to demonstrate what can be gained from reading Shakespeare 'philosophically.'"--Jacket